1980
DOI: 10.1085/jgp.76.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Ionic selectivity, saturation, and block in a K+-selective channel from sarcoplasmic reticulum.

Abstract: A B S T R A C TThe open-channel conductance properties of a voltage-gated channel from sarcoplasmic reticulum were studied in planar phospholipid membranes. The channel is ideally selective for K + over C1-and for K + over Ca ++. In symmetrical 1 M solutions, the single-channel conductance (in pmho) falls in the order: K + (214) > NH~-(157) > Rb § (125) > Na § (72) > Li + (8.1) > Cs + (<3). In neutral bilayers, the channel conductance saturates with ion activity according to a rectangular hyperbolic relation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
143
4

Year Published

1985
1985
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(164 citation statements)
references
References 18 publications
(31 reference statements)
17
143
4
Order By: Relevance
“…This argument is supported by a comparison with the high conductance (Yrmax 230 pS) monovalent cation-selective channel of skeletal muscle SR. In this channel apparent activation enthalpies of 4-6 and 5.3 keal/mol have been determined for K+ and Na+ respectively which are virtually indistinguishable from the values for conductivity of such ions in aqueous solution (4 3-4 5 keal/mol; Coronado, Rosenberg & Miller, 1980). The relative permeability of the sheep cardiac SR calcium-release channel to calciuin and Tris is apparently unaffected by temperature variation, suggesting that the mechanisms governing the affinity of the sites of interaction for these ions are equally sensitive to changing temperature.…”
Section: Discussionmentioning
confidence: 74%
“…This argument is supported by a comparison with the high conductance (Yrmax 230 pS) monovalent cation-selective channel of skeletal muscle SR. In this channel apparent activation enthalpies of 4-6 and 5.3 keal/mol have been determined for K+ and Na+ respectively which are virtually indistinguishable from the values for conductivity of such ions in aqueous solution (4 3-4 5 keal/mol; Coronado, Rosenberg & Miller, 1980). The relative permeability of the sheep cardiac SR calcium-release channel to calciuin and Tris is apparently unaffected by temperature variation, suggesting that the mechanisms governing the affinity of the sites of interaction for these ions are equally sensitive to changing temperature.…”
Section: Discussionmentioning
confidence: 74%
“…While monovalent cation-selective currents are known to exist in ER/SR membrane [10,14,[16][17][18], the identity of gene(s) encoding these channels was completely unknown. TRIC constitutes a candidate gene product for one such long-sought, counter ion channel in the ER/SR membrane.…”
Section: Importance Of Tric In Physiology and Pathophysiologymentioning
confidence: 99%
“…Movement of ions across the SR membrane to counter this negative potential has been implicated in the efficient operation of VICR in skeletal muscle and CICR in cardiac muscle [10][11][12][13][14][15]. Although channels selective for monovalent cations have been reported in SR membrane [10,14,[16][17][18], until recently no gene has been identified that encodes an ER/SR localized cation-selective channel.…”
Section: Introductionmentioning
confidence: 99%
“…Since, a channel that displays a high conductance for K* in the SR membrane has been described and the electrical properties of th. ;s channel well defined [5][6][7]. The physiological role of this K ÷ permeability is still an important question.…”
Section: Introductionmentioning
confidence: 99%